GEMSS: Grid-infrastructure for Medical Service Provision - Benkner, S.; Berti, G.; Engelbrecht, G.; Fingberg, J.; Kohring, G.; Middleton, S. E.; Schmidt, R. (Methods of Information in Medicine, 2005)
Objectives: The European GEMSS Project is concerned with the creation of medical Grid service prototypes and their evaluation in a secure service-oriented infrastructure for distributed on demand/supercomputing. Key aspects of the GEMSS Grid middleware include negotiable QoS support for time-critical service provision, flexible support for business models, and security at all levels in order to ensure privacy of patient data as well as compliance to EU law.Methods: The GEMSS Grid infrastructure is based on a service-oriented architecture and is being built on top of existing standard Grid and Web technologies. The GEMSS infrastructure offers a generic Grid service provision framework that hides the complexity of transforming existing applications into Grid services. For the development of client-side applications or portals, a pluggable component framework has been developed, providing developers with full control over business processes, service discovery, QoS negotiation, and workflow, while keeping their underlying implementation hidden from view.Results: A first version of the GEMSS Grid infrastructure is operational and has been used for the set-up of a Grid test-bed deploying six medical Grid service prototypes including maxillofacial surgery simulation, neuro-surgery support, radio-surgery planning, inhaled drug-delivery simulation, cardiovascular simulation and advanced image reconstruction.Conclusions: The GEMSS Grid infrastructure is based on standard Web Services technology with an anticipated future transition path towards the OGSA standard proposed by the Global Grid Forum. GEMSS demonstrates that the Grid can be used to provide medical practitioners and researchers with access to advanced simulation and image processing services for improved preoperative planning and near real-time surgical support.
Keywords: Computer simulation; computer communication networks; computer security